Influence of annealing temperature on the photocatalytic efficiency of sol-gel dip-coated ZnO thin films in methyl orange degradation - A.H. Haritha; M.E. Cruz; O. Sisman; A. Duran; D. Galusek; J.J. Velázquez; Y. Castro (Open Ceramics)
ZnO thin films on glass substrates and silicon wafers were prepared by the sol-gel dipcoating technique and annealed at temperatures ranging from 300 - 550 °C. X-ray diffraction (XRD) and Raman analysis confirm the hexagonal wurtzite structure of ZnO. Scanning electron microscopy (SEM) examination confirmed that the films were homogeneous, crack-free and with a uniform distribution of nano-sized spherical grains. The decomposition of methyl orange (MO) using a solar simulator was used to determine the photocatalytic activity of the thin films. The annealing temperature was found to have a significant influence on the structure, morphology, and photocatalytic performance of ZnO thin films. The best photocatalytic activity under solar irradiation was shown by the ZnO thin film annealed at 450 °C. The enhanced photocatalytic performance of the films can be attributed to their optimized crystallinity, surface roughness and morphology, which provide more active sites for the photocatalytic reactions.